STRATEGI PENGEMBANGAN PENDIDIKAN NILAI PADA GENERASI MILENIAL - Muchamad Rofiq; Khairul Anam; Mukh. Nursikin (GoAcademica Research dan Publishing, 2022)
The purpose of this paper is to find out the right strategy in value education for the millennial generation. The research used is descriptive analytic, namely using the theories of experts about value education in the space of character formation. Those born in the 1980-2000 range are the millennial generation. This generation has characteristics like Existence, requires more attention, likes to have opinions, grows an image, adds insight, likes freedom, likes to personalize, relies on instant information speed (ready to serve), likes to learn, works in an innovative environment, actively collaborates, hyper technology, critical, confidence, connected, lazy, not deep, not grounded, or not sociable. The results of the study reveal slightly different strategies for teaching values ​​to the Millennial Generation including compassion, inculcating deeper values ​​of the Qur'an and Hadith, inculcating local wisdom values ​​and so on.